2017
DOI: 10.1111/febs.14201
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 targets Smad, p38 MAPK, and PI3K/Akt signaling pathways to induce PFKFB3 gene expression and glycolysis in glioblastoma cells

Abstract: In human cancers, transforming growth factor-β1 (TGF-β1) plays a dual role by acting as both a tumor suppressor and a promoter of tumor metastasis. Although TGF-β1 contributes to the metabolic reprogramming of cancer cells and tumor-associated stromal cells, little is known of the molecular mechanisms connecting this cytokine with enhanced glycolysis. PFKFB3 is a homodymeric bifunctional enzyme, belonging to the family of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatases, that controls the conversion of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 53 publications
5
117
1
1
Order By: Relevance
“…In the present study, we demonstrated that RAB11A could act as a target of miR-302/372/373/520 and found that lnc-SNHG1 played an oncogenic role in pituitary tumor progression by activating the RAB11A/Wnt/β-catenin signaling pathway by regulating the expression of A-β-catenin, c-myc, and cyclin D1. TGF-β/ SMAD3 signaling is a major contributor to the development of many diseases, including renal fibrosis [28], hepatic fibrosis [29], glioblastoma [30], and pulmonary fibrosis [31]. Here, we have demonstrated that lnc-SNHG1 could up-regulate the TGFBR2/SMAD3 pathway by competitively inactivating miR-302/372/373/520 in GH1 and RC-4B/C cells.…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, we demonstrated that RAB11A could act as a target of miR-302/372/373/520 and found that lnc-SNHG1 played an oncogenic role in pituitary tumor progression by activating the RAB11A/Wnt/β-catenin signaling pathway by regulating the expression of A-β-catenin, c-myc, and cyclin D1. TGF-β/ SMAD3 signaling is a major contributor to the development of many diseases, including renal fibrosis [28], hepatic fibrosis [29], glioblastoma [30], and pulmonary fibrosis [31]. Here, we have demonstrated that lnc-SNHG1 could up-regulate the TGFBR2/SMAD3 pathway by competitively inactivating miR-302/372/373/520 in GH1 and RC-4B/C cells.…”
Section: Discussionmentioning
confidence: 70%
“…To understand how PPARγ signaling influences the metabolic phenotype of the TREM2 variants we interrogated PFKFB3 signaling, a key regulatory enzyme involved in glycolytic induction 25,26 and identified as a target of PPARγ. 24 We found that pioglitazone exerted its effects via a p38MAPK/ PFKFB3 signaling cascade and we show that activation of the PPARγ/p38MAPK cascade and PFKFB3 activity is sufficient to rescue the functional deficit in Aβ 1-42 phagocytosis identified in the TREM2 hypomorphic iPS-Mg, a key hallmark associated with AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the mechanisms by which pioglitazone can initiate the switch to glycolysis in TREM2 R47H variants, we probed the involvement of the PPARγ target PFKFB3 (Guo et al, 2010), 24 a key regulatory enzyme in glycolysis. 25,26 PFKFB3 regulates glucose metabolism via the synthesis of fructose-2,6-bisphosphate, a potent allosteric activator of 6-phosphofructo-1-kinase (PFK-1), which catalyzes the committed step of glycolysis through the conversion of fructose-6-phosphate and ATP to fructose-1,6-biphosphate and ADP. 27 The signaling pathway leading to the activation of PFKFB3 is through p38-MAPK-dependent phosphorylation of MK2 and subsequent phosphorylation of PFKFB3 for the induction of the glycolytic switch.…”
Section: Pioglitazone Rescues the Energy Deficits In Trem2 Variant mentioning
confidence: 99%
“…Furthermore, TGFβ1 induced HO-1 promoter activity, and this was increased when NOX4 was expressed in 293T and HepG2 cells ( Figure 6c). NRF2 is known to be a master regulator of cell metabolism, it can contribute to switch from oxidative phosphorylation (OXPHOS) to glycosis (Wang et al, 2018), TGFβ1 induces the expression of one of the glucose transporter, GLUT1, in GBM (Rodríguez-García et al, 2017). We hypothesized that this might be NOX4 dependent.…”
Section: Tgfβ and Pdgf Increase The Proliferation Of Gscs In A Nox4-dmentioning
confidence: 98%